2D multichannel seismic reflection data of RV POLARSTERN cruise PS74, East Greenland Margin, profile AWI-20090300 - Estella Weigelt; Wolfram H Geissler; Andrea Catalina Gebhardt; Wilfried Jokat (PANGAEA, 2025)
The data set provides raw and processed seismic reflection data collected during Expedition PS74 (ARK-XXIV/3) onboard RV Polarstern along the East Greenland Margin in 2009. Detailed data acquisition parameters for the profiles are documented in the expedition report (Jokat, 2010). Metadata, recording parameters, and the seismic data processing sequence are documented in the EBCDIC-Headers enclosed in the seg-y files. Navigation information is included in the seg-y headers, in the Shot-list files and Navigation files (see raw data). A ReadMe file additionally lists the metadata and recording parameters for the seismic profiles. The data set is grouped into three categories: 1. Raw data comprise (a) demultiplexed seismic data in seg-y format, (b) a shot list of date, time and shot-number, and (c) navigation data with date, time, and coordinates. 2. Primary data consist of CDP-sorted data in seg-y format. 3. The data product is provided as stacked version of the seismic profile in seg-y format.